The effect of pre-weaning exposure to soybean meal on subsequent post-weaning growth performance in the early-weaned pig - K G Friesen; Frank Blecha; D N Reddy; P G Reddy; B T Richert; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1991)
Two hundred and forty pigs averaging 11.3 lb and 21 d of age were utilized to determine the effect of pre-weaning exposure to soybean meal on nursery performance. Pigs were derived from sows that were fed either a soybean meal based- or a corn gluten meal based-diet throughout gestation and lactation. Across sow treatments, pigs were stomach-infused with 6 g/d of soybean meal or placebo from d 5 to 9 of age. Treatment structuring prior to weaning allowed for comparisons between pigs immunologically sensitized to soy proteins and pigs nonsensitized to soy proteins. Nursery treatments allowed for a comparison between a diet containing known soy antigens (glycinin and beta-eonglycinin) and a diet that did not contain dietary antigens (milk protein). Thus, eight nursery treatments resulted based upon sow treatment (soybean meal vs corn gluten meal diets), stomach infusion (soybean meal vs placebo), and Phase I dietary treatment (soybean meal vs milk diets). Pigs were allotted by weight and sex within sow treatment by stomach infusion group. Pig weights and feed consumption were recorded weekly for the determination of average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). Sow treatment and infusion treatments did not cause differences in growth performance, allowing data to be analyzed for the main effect of nursery diet treatment. Phase I diets (1.4% lysine) were fed from d 0 to 14 post-weaning. During this time, ADG was increased by 18% in pigs fed a diet containing all milk protein. Average daily feed intake was decreased by 6% and F/G by 24% in pigs fed the soybean meal diet, compared to pigs fed the milk diet. Pigs fed a soybean meal diet during Phase I appeared to respond to the diet with a delayed transient hypersensitivity (DTH) to soy proteins. On d 14, all pigs were placed on a common (1.25% lysine) Phase II diet. This diet contained 22.7% soybean meal and 10% dried whey. Phase II performance was inverse to Phase I performance, with pigs fed a milk diet during Phase I having a 20% decrease in ADG, an 8% decrease in ADFI, and 14% poorer F/G than pigs fed a soybean meal diet during Phase I. These results suggest that the DTH response occurred during Phase II in pigs fed an all milk diet during Phase I. The magnitude of the DTH response was similar for pigs in both phases. The overall performance (d 0 to 35) indicated a 7% decrease in ADG, a 5% decrease in ADFI, with a 2% poorer F/G in pigs fed a milk diet during the Phase I period. These data indicate that pigs develop a tolerance to soy proteins within 2 wk post-weaning. Early-weaned pigs fed a diet devoid of soybean meal for 14 d will exhibit the same DTH response when placed on a corn-soybean meal diet as pigs fed a diet containing soybean meal immediately following weaning. This experiment also points out that prior infusion to soy protein is not necessary for a possible DTH response.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Pig; Starter; Subsequent performance; Transient hypersensitivity; Soybean